2018
DOI: 10.1016/j.ijthermalsci.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stirring influence on solute segregation during plane front directional solidification

Abstract: The present paper focuses on directional solidification processes for photovoltaic silicon purification. The use of a mechanical stirrer in the melt to enhance impurity segregation is investigated through numerical simulations. The 3D forced convection flow is resolved in a transient regime thanks to a sliding mesh approach. The hydrodynamic model is coupled to a solute transport simulation in a quasi-steady approximation (i.e. with constant liquid height). Velocity measurements are performed by Particle Image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In order to optimize the purification of metallurgical grade silicon by directional solidification, a number of active control techniques are used. Among these techniques, we can mention mechanical stirring process [5][6], the use of different types of magnetic fields [7][8], the rotation of the crucible as in the Accelerated Crucible Rotation Technique or vibrational techniques as the Axial Vibration Control using vibrations of the growing crystal or oscillation of a submerged body (see references for these techniques in [9]), and the acoustic streaming (steady flow generated by progressive acoustic waves) [10]. The main objective of these control techniques is to enhance the level of mixing in the melt, in the vicinity of the growth interface, in order to achieve silicon ingots containing less impurities.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the purification of metallurgical grade silicon by directional solidification, a number of active control techniques are used. Among these techniques, we can mention mechanical stirring process [5][6], the use of different types of magnetic fields [7][8], the rotation of the crucible as in the Accelerated Crucible Rotation Technique or vibrational techniques as the Axial Vibration Control using vibrations of the growing crystal or oscillation of a submerged body (see references for these techniques in [9]), and the acoustic streaming (steady flow generated by progressive acoustic waves) [10]. The main objective of these control techniques is to enhance the level of mixing in the melt, in the vicinity of the growth interface, in order to achieve silicon ingots containing less impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Chatelain et al [18] studied the possibility to use a mechanical stirrer. The moving solid-liquid front, however, renders difficult the introduction of a mechanical stirrer, which would have to be progressively removed from the tank.…”
Section: -11mentioning
confidence: 99%
“…[16] also used several ultrasonic sources to increase the geometric complexity of the flow and generate chaotic mixing in a cylindrical container. Our team is interested in improving mixing in parallelepipedic cavities in connection with photovoltaic crystal growth configurations [17,18]. In this context, relying on non-normal reflections of an acoustic beam on the container walls makes it possible to generate several jets with a single acoustic source [19,20], thus leading to 3D flows prone to destabilize and even reach chaotic states [21,22] when increasing the acoustic power introduced in the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Parametric combination for epoxy/kenaf composites preparation by using 2 3 two-level full factorial design strategies The results were averaged from five (5) tested samples of each respective experimental design at different parametric combination. The results had revealed that, at the highest kenaf content of 35 wt.…”
Section: Tablementioning
confidence: 99%
“…Initially, the mechanical mixing by high speed stirring method has widely used in every common thermoset based polymer composites preparation, in order to control the dispersion of filler within the matrix phase [1][2]. This method allows for the formation of higher velocities and strong turbulence within the solution mixture, that desirable for efficient filler segregation in the matrix system [3]. However, according to Sallem et al (2017), the stirring was an important experimental variable that has not been enough explored, particularly for the case of natural fiber based reinforced thermoset polymer composites [4].…”
Section: Introductionmentioning
confidence: 99%